Isolation and Identification of Bacteria Species Associated with the Deterioration of Painted Wall Surfaces in Wukari Metropolis, Taraba, Nigeria, North East - Ogodo Alloysius Chibuike; Danya Sunday; Ibrahim Alhaji Sabo (African Journal of Sciences and Traditional Medicine, 2026)
Wall paintings are among the most expressive forms of human creativity, serving not only decorative purposes but also protecting wall surfaces; however, bacterial colonization of water-based paints can lead to biodeterioration that reduces both durability and aesthetic value. This study aimed to identify and characterize the bacterial species responsible for painted wall degradation using combined conventional microbiological and molecular approaches. Samples were collected by scraping portions of intact and deteriorated painted walls, serially diluted, and cultured on nutrient and MacConkey agars to estimate bacterial loads and isolate different species. Identification and characterization of isolates followed a four-step process comprising macroscopic and microscopic observations, biochemical tests, and sugar fermentation assays. Total bacterial counts ranged from 0.2 × 10⁶ to 2.7 × 10⁶ CFU/g, while coliform counts varied between 0.9 × 10⁶ and 3.6 × 10⁶ CFU/g. Both traditional and molecular analyses identified Bacillus foraminis (CV53), Pseudomonas aeruginosa (PA01), and Staphylococcus aureus as key species associated with paint deterioration, with Bacillus foraminis (69%) being dominant, followed by Pseudomonas aeruginosa (20%) and Staphylococcus aureus (11%). Molecular data further revealed a broader bacterial diversity, including previously unreported taxa, with notable variation among sampling locations. Overall, this study advances the understanding of bacterial ecology on painted surfaces and provides a scientific basis for developing strategies to protect wall paintings and other painted substrates from microbial degradation.